2014
DOI: 10.1021/ja412152x
|View full text |Cite
|
Sign up to set email alerts
|

Absolute and Direct MicroRNA Quantification Using DNA–Gold Nanoparticle Probes

Abstract: DNA-gold nanoparticle probes are implemented in a simple strategy for direct microRNA (miRNA) quantification. Fluorescently labeled DNA-probe strands are immobilized on PEGylated gold nanoparticles (AuNPs). In the presence of target miRNA, DNA-RNA heteroduplexes are formed and become substrate for the endonuclease DSN (duplex-specific nuclease). Enzymatic hydrolysis of the DNA strands yields a fluorescence signal due to diffusion of the fluorophores away from the gold surface. We show that the molecular design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
247
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 371 publications
(278 citation statements)
references
References 40 publications
27
247
1
3
Order By: Relevance
“…PCR is robust and reliable for DNA or RNA detection but requires sophisticated equipment and lengthy protocols. Instead, a one-pot nanoparticle biosensor assay could detect and quantify targets in complex mixtures, which has been demonstrated with superquenching AuNPs (81). Such assays could be kit-based, and users would generally be well skilled; therefore, these types of application are easy to envisage and would fit in easily alongside other research tools and methodologies.…”
Section: Moving Toward Applicationsmentioning
confidence: 99%
“…PCR is robust and reliable for DNA or RNA detection but requires sophisticated equipment and lengthy protocols. Instead, a one-pot nanoparticle biosensor assay could detect and quantify targets in complex mixtures, which has been demonstrated with superquenching AuNPs (81). Such assays could be kit-based, and users would generally be well skilled; therefore, these types of application are easy to envisage and would fit in easily alongside other research tools and methodologies.…”
Section: Moving Toward Applicationsmentioning
confidence: 99%
“…In acute liver failure (ALF), miR-1224 may represent therapeutic target via inhibiting cell proliferation and promoting cell apoptotic [6]. In addition, using DNA-gold nanoparticle probes, miRNA could be better applied in clinical praxis as biomarkers [7]. One research group showed that miR-155-5p, miR-483-5p, and miR-451a may support the early diagnostic value of coronary plaque rupture [8].…”
Section: Introductionmentioning
confidence: 99%
“…Degliangeli et al [15] have proposed a strategy for miRNA quantification based on DNA-AuNPs probes. As shown in Fig.…”
Section: Noble Metal Nanoparticlesmentioning
confidence: 99%